Poor encoding of position by contrast-defined motion - Allen, Harriet A.; Ledgeway, Tim; Hess, Robert F. (Elsevier, 2004)
Second-order (contrast-defined) motion stimuli lead to poor performance on a number of tasks, including discriminating form from motion and visual search. To investigate this deficiency, we tested the ability of human observers to monitor multiple regions for motion, to code the relative positions of shapes defined by motion, and to simultaneously encode motion direction and location. Performance with shapes from contrast-defined motion was compared with that obtained from luminance-defined (first-order) stimuli. When the position of coherent motion was uncertain, direction-discrimination thresholds were elevated similarly for both luminance-defined and contrast-defined motion, compared to when the stimulus location was known. The motion of both luminance- and contrast-defined structure can be monitored in multiple visual field locations. Only under conditions that greatly advantaged contrast-defined motion, were observers able to discriminate the positional offset of shapes defined by either type of motion. When shapes from contrast-defined and luminance-defined motion were presented under comparable conditions, the positional accuracy of contrast-defined motion was found to be poorer than its luminance-defined counterpart. These results may explain some, but possibly not all, of the deficits found previously with second-order motion.